The Power of Effective Geospatial Information Management in South Korea : Development and Application - Ju, Bola; Kelm, Kathrine (World Bank, Seoul, 2020)
Geospatial information technology has emerged as a major contributor to economic transformation for many countries. Established along with the E-government drive, the National Spatial Data Infrastructure (NSDI) in South Korea is especially remarkable, given the fact that South Korea was recently ranked 10th (in 2019) for its geospatial data infrastructure at the global level. Since the formulation of the open government policy in 2013, data were used from a wide range of end users, including the private and public sectors, which facilitated a significant growth in the national market, recording around seven billion US dollars of sales revenue in 2018. This note first introduces geospatial information and its technical evolution in general, then describes the NSDI development plans and strategies, economic impacts on the national market and two geospatial information applications. Finally, the note concludes with the key factors that contributed to the successful development and application of the NSDI, information and innovation.